Beyond scores: Self-efficacy and self-monitoring as mechanisms of project-based learning effects in an analog electronics course - Ilmiyati Rahmy Jasril; Muhammad Anwar; Muhammad Giatman; Andhika Herayono (CV. FOUNDAE, 2026)
Background: Project-Based Learning (PjBL) has been widely adopted in engineering education to improve students’ achievement and engagement; however, most studies remain outcome-oriented and provide limited insight into the psychological mechanisms underlying its effectiveness. In technically demanding courses such as Analog Electronics, understanding how instructional strategies influence internal learning processes is essential for promoting meaningful learning. Aim: This study aims to examine the effect of PjBL on students’ learning achievement and to investigate whether self-efficacy and self-monitoring function as mediating variables linking PjBL to academic performance. Method: A quantitative quasi-experimental design with a pretest–posttest non-equivalent control group was employed, involving 50 undergraduate engineering students (25 in the PjBL group and 25 in the control group). Data were collected using a learning achievement test and validated questionnaires measuring self-efficacy and self-monitoring. Data analysis was conducted using ANCOVA to assess treatment effects and mediation analysis with bootstrapping (5,000 resamples) to examine indirect effects. Results: The results indicated that PjBL significantly improved students’ posttest scores after controlling for prior knowledge. PjBL also significantly increased both self-efficacy and self-monitoring. However, mediation analysis revealed that only self-efficacy had a significant indirect effect on learning achievement, while self-monitoring did not show a unique mediating effect, likely due to its strong correlation with self-efficacy. The direct effect of PjBL on achievement remained significant, indicating partial mediation. Conclusion: The findings suggest that PjBL enhances learning achievement both directly and indirectly through strengthening students’ self-efficacy. This highlights the importance of incorporating motivational support within project-based environments to foster effective and sustainable learning in engineering education.